2019
DOI: 10.1080/15384047.2019.1665954
|View full text |Cite
|
Sign up to set email alerts
|

Diminished S-adenosylmethionine biosynthesis and its metabolism in a model of hepatocellular carcinoma is recuperated by an adenosine derivative

Abstract: S-adenosylmethionine (SAM), biosynthesis from methionine and ATP, is markedly decreased in hepatocellularular carcinoma (HCC) for a diminution in ATP levels, and the down regulation of the liver specific MAT1a enzyme. Its metabolic activity is very important in the transmethylation reactions, the methionine cycle, the biosynthesis of glutathione (GSH) and the polyamine pathway, which are markedly affected in the HCC. The chemo-preventive effect of IFC305 in HCC induced by DEN, and the increase of ATP and SAM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…129 Exogenous SAM can inhibit HCC development by recovering the normal level of SAM. 131 However, 24-day intravenous infusion of SAM did not affect the size of the formed tumors, which may be due to the compensatory induction of GNMT, and prevented SAM accumulation. 38 A study revealed that tumor-initiating cells become addicted to exogenous methionine because of highly elevated methionine cycle activity.…”
Section: Methionine Metabolism and Cldsmentioning
confidence: 88%
See 1 more Smart Citation
“…129 Exogenous SAM can inhibit HCC development by recovering the normal level of SAM. 131 However, 24-day intravenous infusion of SAM did not affect the size of the formed tumors, which may be due to the compensatory induction of GNMT, and prevented SAM accumulation. 38 A study revealed that tumor-initiating cells become addicted to exogenous methionine because of highly elevated methionine cycle activity.…”
Section: Methionine Metabolism and Cldsmentioning
confidence: 88%
“… 129 , 130 During the general development of the fetal liver, the originally expressed MAT2A is gradually replaced by MAT1A. 116 , 131 MAT2A and its gene product, MAT IIα (dimer formed from α2 subunits), are overexpressed in various human epithelial tumors. TNF-α upregulates MAT2A via NF-κB and adaptor-related protein complex 1.…”
Section: Methionine Metabolism and Cldsmentioning
confidence: 99%
“…5 -O-{[3-({4-[(3Aminopropyl)amino]butyl}amino)propyl]carbamoyl}-2 -deoxyadenosine is an adenosine derivative. Adenosine, an essential metabolite distributed in several mammalian tissues [57,58], acts as a ubiquitous endogenous cell signaling and modulator agent since it directly affects a variety of synaptic processes and signaling pathways, thus playing an important role in the regulation of several neurotransmitters in the central nervous system [59]. Moreover, adenosine produced in hypoxic, ischemic, or inflamed environments reduces tissue injury and promotes repair [60].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the two AUBPs AUF1 and HuR have been found to deeply impact the amino acid metabolism in the liver of rats treated with the carcinogen DEN. The levels of S-adenosylmethionine (SAM) were indeed decreased by the activity of these two AUBPs, which regulate the gene expression of methionine adenosyltransferase 1a and 2a ( Mat1a and Mat2a ) [ 176 ]. Of importance, a metabolic switch from Mat1a to Mat2a expression, which translates into the downregulation of SAM levels, is a well-known metabolic reprogramming event favoring HCC progression.…”
Section: Aubps In the Hallmarks Of Liver Cancermentioning
confidence: 99%